Prevalence of Strongyloides in Southeast Asia: a systematic review and meta-analysis with implications for public health and sustainable control strategies - Abigail Hui En Chan; Teera Kusolsuk; Dorn Watthanakulpanich; Wallop Pakdee; Pham Ngoc Doanh; Azlin Mohd Yasin; Paron Dekumyoy; Urusa Thaenkham (BMC, 2023)
Abstract Background Strongyloidiasis, caused by the nematodes Strongyloides stercoralis and Strongyloides fuelleborni, is estimated to affect over 600 million individuals worldwide. The disease is endemic in Southeast Asia, where a warm-humid climate and socio-economic conditions maintain the parasite's life cycle and transmission. However, the current diagnostic methods may not be sufficiently sensitive, suggesting that the true prevalence of strongyloidiasis could be seriously underestimated in this. This study aims to determine the prevalence of strongyloidiasis in Southeast Asia through a systematic review and meta-analysis and to discuss the implications of the estimated prevalence on diagnostic approaches and control strategies. Methods Following PRISMA guidelines, we conducted a systematic literature search in PubMed and Google Scholar databases to identify studies reporting Strongyloides prevalence data in the 11 Southeast Asian countries up to December 2022. A random effects model was employed to estimate the pooled prevalence of S. stercoralis at both regional and country levels. Results Out of 3722 articles identified, 224 met our inclusion criteria. For S. stercoralis specifically, we found 187 articles, of which 52.4% were from Thailand. All Southeast Asian countries, except Brunei, had at least one study on Strongyloides prevalence. The estimated pooled prevalence of S. stercoralis regionally was 12.7% (95% CI 10.70-14.80%), ranging from 0.4 to 24.9% at the country level. Cambodia had the highest pooled prevalence (24.9%, 95% CI 15.65-35.38%), followed by Lao PDR (16.5%, 95% CI 9.50-24.95%). Moreover, we obtained a pooled prevalence of 10% (95% CI 7.06-13.52%) in a group comprising immigrants, workers, and veterans from Southeast Asian countries. S. stercoralis infects various host types, including nonhuman primates, domestic dogs and cats, rodents, and transport carriers such as cockroaches and vegetables. Conclusions A high prevalence of strongyloidiasis in Southeast Asia was revealed, highlighting the importance of the region's ongoing research, surveillance, and control efforts. Factors contributing to the strongyloidiasis transmission include the role of animal hosts, the impact of global connectivity, and the significance of the co-endemicity of other Strongyloides species. Based on these findings, a multi-pronged One-Health approach is essential for sustainable intervention and control.